Toponymic Persistence: The Proto-Indo-European *kar- Root in the Pre-Latin Ligurian Context* - Perono Cacciafoco, Francesco (2016)
This paper provides a survey on the proto-Indo-European root *kar-/ *kal- ‘stone, rock’ and on the related European prehistoric toponymy following a new convergent approach. The stem *kar- is considered as a presumably pre-Indo-European root transferred (after the possible arrival of the Indo-Europeans to the European territories) into the linguistic system of proto-Indo-European through a process of re-use and re-functionalization of roots and (loan-)words due to linguistic contact. Phonetically adapted to the (proto-)Indo-European standards, the root *kar- shows, at least in the Ligurian area, a variant *kal- (not an independent stem, but an alternative form) involved in the formation of a number of words and place names linked to the notions of ‘rock’ and ‘stone’ (in particular, ‘friable, calcareous rock eroded by water’). The paper tries, moreover, to highlight a particular morphologic phenomenon of reduplication of the root *kar- (although the reduplication is not widely productive in Indo-European) in the Italian (Ligurian) place name Carcare (< Carcaris).